2005
DOI: 10.1016/j.seizure.2005.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Steroids in intractable childhood epilepsy: Clinical experience and review of the literature

Abstract: Steroids and adrenocorticotrophic hormone (ACTH) have been used for the treatment of infantile spasms for several years. However, the use of steroids in the treatment of epilepsy beyond infantile spasms has been limited to only a few studies. We report the experience with steroids in 32 children with intractable epilepsy, not including West syndrome. In 47% there was a decrease in seizure frequency, 25% became seizure free, 11% had a seizure reduction of >50% and 11% had a seizure reduction of <50%. Our study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 31 publications
(52 reference statements)
5
78
2
1
Order By: Relevance
“…The authors suggested that corticosteroids offered better efficacy and longer lasting anticonvulsant action than conventional anti-epileptic drugs. Similar data have been reported elsewhere as well [20,21]. The authors [20,21] concluded that steroid treatment of epilepsy remains yet undefined and needs further studies.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…The authors suggested that corticosteroids offered better efficacy and longer lasting anticonvulsant action than conventional anti-epileptic drugs. Similar data have been reported elsewhere as well [20,21]. The authors [20,21] concluded that steroid treatment of epilepsy remains yet undefined and needs further studies.…”
Section: Introductionsupporting
confidence: 84%
“…Similar data have been reported elsewhere as well [20,21]. The authors [20,21] concluded that steroid treatment of epilepsy remains yet undefined and needs further studies. Acknowledging this line of evidence, the aim of the present study was to investigate the effect of steroid adrenal and gonadal hormones on the intensity, dynamics and latency of kainic acid-evoked seizure and lethality in a rat model of epileptogenesis.…”
Section: Introductionsupporting
confidence: 84%
“…These findings are similar to those of Sinclair, 9 who found that 46% of 28 children older than 1 year with intractable epilepsy became seizure free and another 40% showed significant reductions in seizure frequency when prednisolone was given at 1 mg/kg per day for 12 weeks (this included 6 weeks of daily therapy and 6 weeks of treatment on alternate days). The report of Verhelst et al, 10 containing data on 36 patients (a heterogeneous pediatric population with intractable epilepsies of diverse etiologies) who underwent various steroid treatments, showed somewhat less favorable results. Although 25% of patients became seizure free and 11% showed reductions in seizure frequency of 450%, the authors concluded that steroids were effective as adjunctive treatments for children with intractable epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…In Sinclair's study, 9 it was unclear how long the improvement achieved with prednisolone therapy was maintained. In the work of Verhelst et al, 10 two-thirds of patients who became seizure free relapsed. Oguni et al reported only transient improvements in myoclonic and absence seizures in a few patients treated with ACTH.…”
Section: Article In Pressmentioning
confidence: 96%
See 1 more Smart Citation